FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN USER DALAM PEMBELIAN RUMAH PADA PERUMAHAN MULTI NIAGA TOWN HOUSE - Dirwan Dirwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
Human needs is getting increasingly diverse, and one of them will need places to live that home. One of the developers of Home PT. Multi Sao Asri housing that offers one of the Commercial Multifunction Residential Town House. However, per the researches issues facing that is how home sales may continue to increase every year, whereas now this emerging housing developers who dared bring up the terobo san-new breakthrough. Therefore, the researcher's will be updating the analysis of the factors that are considered essential for the examined factors such as location, facilities, income and lifestyle against the verdict of the purchase. This research uses a multiple linear regression analysis with SPSS program Version 21.0. The population is all of the residents in residential Commercial Multifunction Town House. While the samples used as many as 40 people by the method of proportional sampling. Research on testing the influence of factors (location, facilities, income and lifestyle) produces the value t calculate > t table so that the alternative hypothesis (HA) received and the zero hypothesis (H0) denied that indicates the free variables affect positive toward purchasing decisions, and the most dominant factor over purchasing decision factor is location. In this study also produces's 67.5% free variables for which the positive spirit towards berpenga purchase decisions and the remaining 32.5% is the influence of other factors not included in this research. Based on data obtained from this research it can be drawn the conclusion that partially variable locations, facilities, income and lifestyle affect the decision of buying a home on Commercial Multifunction residential Town House, and the most dominant factors affect the decision of the user in performing the pem proof factor is location. A few suggestions that may be put forward by researchers is the developer of the housing should improve the quality of public facilities and facility diperumahan Multi Niaga Town House.